Elective neck dissection versus "wait and watch" policy in tongue carcinoma - Satish Kumaran Pugazhendi; Lalitha Thambiah; Anuradha Venkatasetty; Vinod Thangaswamy (Wolters Kluwer Medknow Publications, 2012)
Aim: To evaluate the efficacy of elective neck dissection versus the "wait and watch" policy in the treatment of early squamous cell carcinoma of tongue. Materials and Methods: This is a retrospective study of 21 patients with surgical treatment between April 2009 and July 2011. The patients were divided into two groups, with Group 1 consisting of patients who underwent wide excision glossectomy with elective neck dissection and Group 2 consisting of patients who underwent glossectomy without the neck being surgically addressed. The selection of patients was done by the random double-blinded method and the review was done by a single reviewer. All patients were examined for an average period of 1 year postoperatively. Results: Twenty-one cases were treated, among which there were 17 T1 and 4 T2 carcinomas. All the patients had primary carcinoma involving only the tongue with no clinical neck palpable neck nodes. Eleven patients underwent wide excision of primary tumor with elective neck dissection (Group 1) and 10 patients underwent only resection of primary tumor without the neck being surgically addressed (Group 2). In Group 1, there were no recurrences, and in Group 2, there were two patients who developed subsequent cervical node metastasis with one patient undergoing further surgery to address the positive neck and the other patient was lost to follow-up. Conclusions: Regional recurrence was the most common cause of failure after surgical treatment of oral tongue carcinoma. Elective neck dissection significantly reduced mortality due to regional recurrence and also increased the overall survival. Our study suggests that elective neck dissection is a treatment strategy of choice for stages I and II carcinoma of the oral tongue. A prospective, randomized study is worthwhile to further evaluate the benefit of elective neck dissection in the treatment of early carcinoma of the tongue with a larger pool of patients and a lengthier follow-up period.